SYNTHESIS OF EMPTY FRUIT BUNCHES CARBON POLYMER COMPOSITES AS GAS DIFFUSION LAYER FOR ELECTRODEMATERIALS - Nanik Indayaningsih; Anne Zulfia; Dedi Priadi; Evvy Kartini (Center for Science & Technology of Advanced Materials - National Nuclear Energy Agency, 2013)
SYNTHESIS OF EMPTY FRUIT BUNCHES CARBON POLYMER COMPOSITES AS GAS DIFFUSION LAYER FOR ELECTRODEMATERIALS. Empty Fruit Bunches (EFB) of oil palmhas been used, for example, for biofuels, automotive components, particle board, as a carbon source. Carbon material scan be widely used for many applications, for hydrogen storage, conductive or reinforcement plastics, catalyst supports, batteries and fuel cells. In this study, EFB carbon powder has been used as a raw material to make sheets of carbon-polymer composites. The composition of the composite sheet was varied, the electrical properties of the sheets were measured to determine the potential application as a Gas Diffusion Layer for Proton Exchange Membrane Fuel Cell (PEMFC) electrodes. Composites made with carbon composition weight % compared to the polymer are 65/35, 70/30, 75/25 and 80/20. The materials used is EFB carbon powder as a result of the pyrolysis temperature of 900 °C for 1 hour, then crushed and sieved to 200 mesh size, and the polymer was ethylene vinyl acetate. The rawmaterials are mixed in a solvent xylene, and printed using tape casting method, then dried at room temperature. The electrical properties were tested using a HIOKI 3522-50 LCR meter HiTESTER The measurement results show that the greater the ratio of carbon to polymer, the higher the electrical conductivity, the values are between 1.54 S/m-11.34 S/m.Morphology of the composite sheet was observed using Scanning Electron Microscope (SEM) to determine the distribution of carbon and polymer. According to the measurement of morphology and electrical conductivity, the composite is suitable for the gas diffusion layer of the PEMFC electrode.